2020
DOI: 10.1016/j.canlet.2020.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus insertions identify the PIM family of serine/threonine kinases as targetable driver genes in head and neck squamous cell carcinoma

Abstract: Human papillomavirus (HPV) insertions in cancer genomes have been linked to various forms of focal genomic instability and altered expression of neighboring genes. Here we tested the hypothesis that investigation of HPV insertions in a head and neck cancer squamous cell carcinoma (HNSCC) cell line would identify targetable driver genes contributing to oncogenesis of other HNSCC. In the cell line UPCI:SCC090, HPV16 integration amplified PIM1 serine/ threonine kinase gene ~16-fold, thereby increasing transcript … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…Broutian et al observed HPV insertions flanking a 16-fold somatic amplification of the gene PIM1 (Proviral insertion site for Moloney murine leukemia virus MuLV) in the HNSCC cell line UPCI:SCC090, in which more integration sites have been identified [8,22]. This amplification was accompanied by an increase of PIM1 transcripts [81]. PIM1 overexpression has been identified in HNSCCs and has been associated with poor survival [82][83][84].…”
Section: Deregulated Expression Of the Targeted Gene By Hpv Integrationmentioning
confidence: 99%
“…Broutian et al observed HPV insertions flanking a 16-fold somatic amplification of the gene PIM1 (Proviral insertion site for Moloney murine leukemia virus MuLV) in the HNSCC cell line UPCI:SCC090, in which more integration sites have been identified [8,22]. This amplification was accompanied by an increase of PIM1 transcripts [81]. PIM1 overexpression has been identified in HNSCCs and has been associated with poor survival [82][83][84].…”
Section: Deregulated Expression Of the Targeted Gene By Hpv Integrationmentioning
confidence: 99%
“…Documented cooperative interactions between HPV E6 and MYC in inducing telomerase ( hTERT ) expression and keratinocyte immortalization further support the pathophysiological significance of viral integration at this hotspot (Zhang et al 2017). Moreover, we have shown that genetic knockdown or small molecule inhibition of PIM1 induces cell death in UPCI:SCC090, a head and neck cancer cell line in which HPV integrants directly flank a 16-fold amplification of PIM1 (Broutian et al 2020). These archetypal, experimentally tractable examples each illustrate the contributions of HPV integrant-mediated transcriptional alterations to cellular transformation and the malignant phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Our results prove that PIM-1 may function as an oncogene in CC, and PIM-1 may exert its carcinogenic effects through activating the EGFR signaling via increasing the proliferation and decreasing the apoptosis of CC cells. The PIM kinases were first reported as most significantly up-regulated genes during the process of embryonic development 9,15 ; however, in recent years, PIMs were also found to be over-expressed in several cancers. The role of PIM-1 as an oncogene has been investigated in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…The PIM kinases were first reported as most significantly up-regulated genes during the process of embryonic development 9 , 15 ; however, in recent years, PIMs were also found to be over-expressed in several cancers. The role of PIM-1 as an oncogene has been investigated in different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation